Entrepreneurship and Growth An International Historical Perspective - Tortella, Gabriel. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
A collection of eight articles by 17 specialists, this volume provides very recent research on the factors which contribute to the build up of entrepreneurship. Offers an international, comparative and historical perspective, with a special focus upon the Mediterranean.